Policy reforms and incentives in rice production in Bangladesh - Sheikh Selim; Naima Parvin (Cardiff University, Cardiff Business School, 2007)
We estimate an institutional production function to capture incentive induced growth in total factor productivity (TFP) of rice production in Bangladesh. The incentive component of TFP assists in explaining farmers' response to incentives due to major policy reforms during 1980s and 1990s.
Keywords: C33; C51; O13; Q12; 330; Bangladesh; Incentives; TFP; Produktivität; Ökonomischer Anreiz; Reisanbau; Schätzung; Bangladesch